Experimental Infection of Bundibugyo Virus in Domestic Swine Leads to Viral Shedding with Evidence of Intraspecies Transmission - Lewis, Charles E.; Pinette, Mathieu M.; Lakin, Steven M.; Smith, Greg; Fisher, Mathew; Moffat, Estella; Embury-Hyatt, Carissa; Pickering, Brad S. (Transboundary and emerging diseases, 2024)
The Ebolavirus genus contains several of the deadliest zoonotic viruses known. One of these, Bundibugyo virus (BDBV), has been the causative agent of two outbreaks of human disease that have resulted in 211 known cases with a case fatality rate of 33.6%. Although bats are routinely implicated as the possible reservoir species for the ebolaviruses, the source of infection for index cases in almost all outbreaks is unknown with only limited epidemiological evidence directly linking human cases to bats. This lack of evidence leaves open the possibility that maintenance of one or more of these viruses could involve multiple host species or more complex spillover dynamics. Domestic pigs have been found naturally infected with Reston virus (RESTV) and are experimentally susceptible to infection with Ebola virus (EBOV), two other members of the Ebolavirus genus. Infection of pigs resulted in shedding of infectious virus with subsequent transmission to naïve animals being documented, including transmission to humans for RESTV and to nonhuman primates for EBOV. The susceptibility and subsequent viral shedding and pathogenesis of domestic pigs to other ebolaviruses and the potential role this species may play in virus ecology, spillover dynamics, and human public health risk is unknown. For these reasons, we conducted a series of studies aimed at determining the susceptibility of domestic pigs to BDBV thereby demonstrating that pigs are not only susceptible to experimental infection but that the development of productive infection, tissue dissemination, and shedding of infectious virus can also occur while animals remain clinically normal. The role of pigs as a possible interim or amplifying host for ebolaviruses is a concern for both human public health and food security.